2012
DOI: 10.5539/ass.v8n3p169
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Internet Use in Saudian's Small and Mediums Enterprises

Abstract: Employing the Internet as a tool can help address some of the critical issues affecting SMEs in Kingdom of Saudia Arabia, such as increased global competition, increased consumer demand for quality, increased partnerships between large/intermediate and small businesses, rapidly changing market environment, growing need for immediate access to current business information from a variety of sources, The purpose of this study was to assess the current level of Internet usage as a business tool by SMEs that formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…SMEs have an essential role to play in achieving the goals of the Saudi economy, which contributes to the diversification of production and employment of citizens affecting the future of the kingdom and its youth. Small-and medium-sized enterprises (SMEs) are a vital component of the country's economy for several reasons, including their potential to provide employment opportunities and reduce unemployment rates, particularly among the youth, relieving pressure from the public sector [32]. The latest data available in October 2021 showed that approximately five million individuals were employed by SMEs in the Kingdom.…”
Section: Small-and Medium-sized Enterprises (Smes) In Saudi Arabiamentioning
confidence: 99%
“…SMEs have an essential role to play in achieving the goals of the Saudi economy, which contributes to the diversification of production and employment of citizens affecting the future of the kingdom and its youth. Small-and medium-sized enterprises (SMEs) are a vital component of the country's economy for several reasons, including their potential to provide employment opportunities and reduce unemployment rates, particularly among the youth, relieving pressure from the public sector [32]. The latest data available in October 2021 showed that approximately five million individuals were employed by SMEs in the Kingdom.…”
Section: Small-and Medium-sized Enterprises (Smes) In Saudi Arabiamentioning
confidence: 99%